Hubungan Motivasi dan Insentif Dengan Kinerja Kader Posyandu - indah kumala sari (Stikes Syedza Saintika Padang, 2018)
ABSTRACT Performance was an accomplished or accomplished achievement. Based on the observation of the researcher, the reality shows that there are posyandu that have limited cadres so that the service is not running smoothly. The purpose of this research is to determine whether there is a relationship of Motivation and Incentives with Posyandu Nagari Aripan’s.The design of the research is Descriptive Analytic with Cross Sectional Study. The research conducted in Nagari Aripan, area of Puskesmas Singkarak on August 7thto15th2017. Sampling consist of 30 respondents with total sampling technique. Data collection was obtained from the primary data trough interviews using a questionnaire, processed by computerization. For the results of statistical analysis univariate and bivariate used the chi-square test. Univariate analysis prove that more than half 60,0% respondents had low performance, 56,7% respondents had low motivation, and 53,3% respondents were satisfied with the incentive. Bivariate analysis prove there is relationship between motivation and cadres performance with pvalue 0,013 <0,05 and there is relationship between incentives with cadre performance with pvalue 0,001<0,05. This research is expected to give an advice for puskesmas in guidance and planning to improve the performance of posyandu cadres, increase the posyandu cadres to remain active in posyandu activities.It is suggested that training activities for posyandu’s cadres are required, so that posyandu activities can do well.